Building bridges between scholars and the law: A Prerequisite for an innovative society - Hassan, Azmi (2013)
Scholars in Malaysia are full aware of the variety of rules and regulations that effectively take away their academic freedoms thus making it difficult to carry out their teaching and research responsibilities, in a creative and innovative way.The oath of allegiance for example is considered oppressive because it is related to the statutory Bodies (Discipline and Surcharge) Act 2000. This act in effect makes it an offence for any scholars to comment on governmental policies (whether favorably or critically) without appropriate permission.It is highly impractical for the authorities to process the requests from all scholars every time they wish to make a statement or write an article that touches upon governmental policies.Therefore, one can only presume that this law is meant to be used as and when the authorities wish to.That is to say it becomes prevalent and ever present threat to all academics.There is no denying that academic freedom is the core value of creating an open and innovative society a prerequisite for a sustainable economy.Without academic freedom, the dissemination of information will suffer.The general public depends on the academe to provide unbiased views on social and economy analysis so as to strengthened civil society. This can only be achieved if only freedoms of expression are enjoyed by the scholars.This paper will discussed the restrictions and regulations imposed by various regulations, all of which curtail the scope and freedom of research and teaching.Many scholars still shy away from speaking out or approaching government officials to voice their concerned of their area of expertise.